Religious faith, academic stress, and instrumental drug use in a sample of Western-African University students. Issue 2 (August 2018) - Wolff, Wanja; Boama, Sandra Asantewaa
Abstract: Background: Neuroenhancement (NE), the use of substances in order to improve cognitive performance, has received considerable scientific attention in recent years. Broadening this NE concept, people can use drugs as instruments (DI) to improve various aspects of performance. Whereas such functional drug use is well-researched in Western countries, there is a lack of research on this phenomenon in African countries. Objectives: We will provide a first estimate of the frequency by which freely available lifestyle drugs, prescription drugs, and illicit drugs are used for DI and NE purposes in a sample of Western-African university students. Further, we investigate the association of religious faith and academic stress with functional drug use. Methods: Participants were 669 (mean age 22.58 ± 3.89 years) university students from Ghana. Academic stress and religious faith were measured using self-reports. DI – and its' facet NE - was measured with a questionnaire that assesses the lifetime prevalence of 3 × 9 DI combinations. Results: The frequency of DI varied as a function of the specific drug × goal combination between 0.6% and 24.7%. Religious faith was associated with less DI for all measured substance classes and academic stress was only associated with prescription drug DI. Religious faith and academic stress interacted in predicting lifestyle drug DI and prescription drug DI. Conclusions: In general, the frequency of DI in Ghanaian students was markedly lower than in Western samples and this was also the case for DI goals most closely related to NE. In addition, religious faith was associated with less drug use, supporting the claim that religion might serve as a buffer against drug use.